2018
DOI: 10.3390/coatings8100350
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Soft Materials to Rough Surfaces: Experimental Studies, Statistical Analysis and Modelling

Abstract: Adhesion between rough surfaces is an active field of research where both experimental studies and theoretical modelling are used. However, it is rather difficult to conduct precise experimental evaluations of adhesive properties of the so-called anti-adhesive materials. Hence, it was suggested earlier by Purtov et al. (2013) to prepare epoxy resin replicas of surfaces having different topography and conduct depth-sensing indentation of the samples using a micro-force tester with a spherical smooth probe made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…They used the Lennard-Jones potential for calculating van der Waals forces between elements (Medina and Dini, 2014). Recently an indentation test of spheres with microforce tester showed that the highest pull-off force was found not on the smooth sample but that with micro roughness (Pepelyshev et al, 2018). It was argued that the increase of the contact area is the main cause for the increase pull-off force.…”
Section: Adhesive Contact Of a Parabolic Indenter With A Random Roughmentioning
confidence: 99%
“…They used the Lennard-Jones potential for calculating van der Waals forces between elements (Medina and Dini, 2014). Recently an indentation test of spheres with microforce tester showed that the highest pull-off force was found not on the smooth sample but that with micro roughness (Pepelyshev et al, 2018). It was argued that the increase of the contact area is the main cause for the increase pull-off force.…”
Section: Adhesive Contact Of a Parabolic Indenter With A Random Roughmentioning
confidence: 99%
“…Indeed, as it follows from Tables 1, 2, the R rms measured by AFM was below 1.5 nm for the biased a-C sample and below 10.5 nm for the non-biased a-C sample. As it has been recently shown for such small roughness (Pepelyshev et al 2018), a soft counterpart surface may create a full contact. Hence, in such problems only the microscale roughness will govern the contact.…”
Section: Resultsmentioning
confidence: 80%
“…The main methods for testing for normality are the following tests: Kolmogorov-Smirnov (KS), Lilliefors (LF), Shapiro-Wilk (SW), Anderson-Darling (AD), Cramervon Mises (CVM), the Pearson, and Shapiro-Francia (SF). These tests were already used for checking normality of grinding surfaces (Borodich et al, 2016) and surfaces of replicas of polishing paper samples (Pepelyshev et al, 2018). Here we will present the tests for the sake of completeness.…”
Section: Statistical Approaches To Rough Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also need to underline the importance of surface roughness and consideration of related changes in real contact area that can affect adhesion. Experiments of Purtov et al [15] and modelling of the experiments by Pepelyshev et al [16], employing Galanov's model of adhesion between rough surfaces [17], showed that consideration of real contact area is a very important factor in adhesive contact problems. This statement is also nicely confirmed by the analysis of nanoscale static friction by Polyakov et al [18], and various works that demonstrate the influence of roughness on the value of adhesive pull-off force (e.g., [19][20][21]).…”
Section: Introductionmentioning
confidence: 99%